PENGARUH LATIHAN SHADOW MENGGUNAKAN LAMPU REAKSI TERHADAP KELINCAHAN KAKI ATLET PB.ASJAD - Alwahidia, Alwahidia; Supriatna, Eka; Perdana, Rahmat Putra (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
Badminton is one of the game sports favored by the community, which is played by 2 or 4 opposing players using rackets, nets, and shuttlecocks. This sport requires good foot agility to facilitate reach during play. However, in the implementation of exercises for leg agility, it is rarely done so that this affects performance during matches. This study aims to determine the effect of shadow training using reaction lights on the agility of badminton athletes' feet. Experiments were carried out using One-Group Pretest-Posttest Design. The sampling technique used is purposive sampling so that the sample in this study amounted to 10 badminton athletes PB.ASJAD. The data collection technique used a shadow test for 30 seconds and analyzed using the SPSS 26 paired sample test. The results showed that there had been an increase in the average posttest score compared to the average pretest score with a significant increase. Thus, it can be concluded that shadow training using reaction lights has a positive effect on increasing the agility of badminton athletes